Diet and prostate cancer risk reduction. Issue 1 (January 2008) - Cheung, Eric; Wadhera, Panikar; Dorff, Tanya; Pinski, Jacek
Prostate cancer is the most commonly diagnosed malignancy in males. The current body of literature supports the role of nutritional products in the reduction of prostate cancer. This review critically addresses the natural products with the greatest potential to reduce the risk of prostate cancer, including lycopene, vitamin E, selenium, vitamin D, soy and green tea. The toxicities of the dietary products are addressed. The direction of future studies lies in clarifying the effects of these products and exploring the biological mechanisms responsible for the prevention of prostate cancer.